Conclusion: notions of the secular - Karis, Tim; Buß, Johanna (Journal of religion, media and digital culture, 2018)
This conclusion summarises and compares the two preceding case studies: “Secular Voices on Air: The British Debate on Thought for the Day” (Tim Karis) and “The Understanding of dharmanirapekṣa (“secular”) in the Nepali Online Newspaper Nagarik” (Johanna Buss).